Identification of earthworm species in sand‐topdressed hybrid bermudagrass golf tees. Issue 1 (22nd September 2021) - Boyle, Paige; Savin, Mary; Richardson, Michael; Karcher, Douglas E.
Abstract: On golf courses, casting – the egestion of feces – by earthworms on the turfgrass surface can affect playability, growth, and maintenance. The earthworm species responsible for surface casting vary depending on location, climate and weather, soil texture, and turfgrass management practices. The objective of this study was to determine earthworm density and species composition in native soil and sand‐based golf tees managed under different sand topdressing rates (heavy at 2.54 cm yr –1 or light at 0.64 cm yr –1 ) in Fayetteville, AR. Earthworms were collected December 2016 by hand sorting and identified using DNA extraction and sequencing. Light sand topdressing resulted in significantly greater earthworm density. Soil rootzone did not affect earthworm density, which may have resulted from variability in earthworm populations sampled. All communities were comprised primarily of Diplocardia spp.; however, lightly topdressed treatments included Bimastos parvus (Eisen, 1874) and both topdressing treatments included Microscolex phosphoreus (Dugès, 1837). Amynthas spp. were present in all treatments except the heavily topdressed native soil treatment. Core Ideas: Rootzone soil texture did not affect earthworm density. Diplocardia spp. were the dominant earthworm species present in all treatments. Bimastos parvus, Microscolex phosphoreus, and Amynthas spp. were also identified.